Political governance, corruption perceptions index, and national dynamic energy efficiency. (1st May 2021) - Lu, Wen-Min; Kweh, Qian Long; Nourani, Mohammad; Lin, Cheng-Yi
Abstract: This study estimates national dynamic energy efficiency of 49 countries for the period of 2007–2016 by using a dynamic data envelopment analysis model and explores (i) the relationships between the CPI and national dynamic energy efficiency, (ii) political governance and CPI, (iii) political governance and dynamic energy efficiency, and (iv) the mediating role of the CPI on the association between political governance and national dynamic energy efficiency. Empirical results corroborate that European and high-income countries perform better than their counterparts in national dynamic energy efficiency and the CPI, which has a positive effect on national dynamic energy efficiency. The proxies of political governance, such as political stability, bureaucratic quality, personal safety and security of private property, and legal and regulatory frameworks, also affect CPI and national dynamic energy efficiency, respectively. The CPI has a mediating effect on the relationship between political governance and national dynamic energy efficiency. Overall, this study suggests that governments can promote probity policies to further improve national dynamic energy efficiency. Graphical abstract: Image 1 Highlights: We measure national dynamic energy efficiency of 49 countries. CPI significantly leads to low national dynamic energy efficiency. We decompose political governance into three components from 2007 to 2016. Political governance affects CPI and national dynamic energy efficiency. The CPI mediates the link between political governance and dynamic efficiency.